Antioxidant activity and nutritional value of Citrus limetta and Ananas comosus pomace - Preeti Chanalia; Dimpi Gandhi; Anjana; Suman Bala; Jasbir Singh; Suman Dhanda (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2018)
Pulp waste from two fruits, Citrus limetta and Ananas comosus were analysed for in vitro antioxidant activity, total carbohydrate and pectin content and ascorbic acid. Total polyphenols determined in terms of catechol equivalents per 100g of pomace were higher in Citrus limetta (63-112 mg of catechol equivalents/100g pomace) as compared to Ananas comosus (22-86 mg of catechol equivalents/100g pomace). Polyphenols were higher in methanol extract of both the fruit pomace as compared to other extracts. Antioxidant activity was determined in terms of reducing power and there was no signifi cant difference in antioxidant activity of the two fruits. Total carbohydrate content determined was 14-70 mg glucose equivalents/100g pomace for Citrus limetta and 42-71 mg glucose equivalents/100g pomace for Ananas comosus pulp waste. Citrus limetta pomace was relatively rich in ascorbic acid (16mg/100g pomace) and pectin (213 mg/g pomace) as compared to Ananas comosus. Thus, this study reveals biowastes of these two fruits from the food industry can be utilized further.